2013
DOI: 10.1021/nn400894d
|View full text |Cite
|
Sign up to set email alerts
|

Shedding Light on Vacancy-Doped Copper Chalcogenides: Shape-Controlled Synthesis, Optical Properties, and Modeling of Copper Telluride Nanocrystals with Near-Infrared Plasmon Resonances

Abstract: Size- and shape-controlled synthesis of copper chalcogenide nanocrystals (NCs) is of paramount importance for a careful engineering and understanding of their optoelectronic properties and, thus, for their exploitation in energy- and plasmonic-related applications. From the copper chalcogenide family copper telluride NCs have remained fairly unexplored as a result of a poor size-, shape-, and monodispersity control that is achieved via one-step syntheses approaches. Here we show that copper telluride (namely C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
273
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(288 citation statements)
references
References 57 publications
12
273
3
Order By: Relevance
“…5d). 29 On the other hand, the work of Li et al More in general, they were able to show that oxidizing conditions, which would increase the number of free carriers, are indeed translated into an increased conductivity of a film of Cu 2Àx S NCs. The conductivity could be then reversibly decreased under reducing conditions.…”
Section: Review Article Chem Soc Revmentioning
confidence: 97%
See 1 more Smart Citation
“…5d). 29 On the other hand, the work of Li et al More in general, they were able to show that oxidizing conditions, which would increase the number of free carriers, are indeed translated into an increased conductivity of a film of Cu 2Àx S NCs. The conductivity could be then reversibly decreased under reducing conditions.…”
Section: Review Article Chem Soc Revmentioning
confidence: 97%
“…63 Imaging, sensing and photothermal therapy do not conclude the range of potential application for copper chalcogenide NCs. NCs of these materials, because of their intrinsic ability to undergo cation exchange, 64 29 This suggests that a large fraction of the holes in these copper-deficient chalcogenides is actually localized. It was therefore concluded that the shape of the NCs has little influence on their plasmonic response.…”
Section: Review Article Chem Soc Revmentioning
confidence: 99%
“…We exploit the well-known chemical sensitivity of copper(I) sulfide, [17] which can be summarized by the chemical reaction: [18] Cu 32 S 16 Ð Cu 32-n S 16 …”
mentioning
confidence: 99%
“…We hypothesized that the addition of amines, which bind strongly to copper, should assist in extracting copper from the copper sulfide lattice, thus pushing the equilibrium indicated in Equation [2] to the right. More copper-deficient stoichiometries (Cu 30 S 16 , Cu 29 S 16 , and so on) are also possible. [21] Upon addition of amine to stoichiometric copper sulfide nanocrystals, we observed that a strong LSPR mode appeared.…”
mentioning
confidence: 99%
See 1 more Smart Citation